Literature Circles to Improve Reading Motivation and Skill - Nurhaeda Gailea; Sutrisno Sadji Evenddy; Hani Haeroni (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The objective of this research is to find out the improvement of reading motivation and skill by using literature circles. The researcher used classroom action research. The sample of this research were the eleventh grade of SMAN 1 Cinangka students. The researcher found that there is a significant improvement in reading motivation and skill by using literature circles. In the first cycle, students reading skill improved 42,9%, and the students reading motivation improved 41,%. In the second cycle gradually students reading skill improved 68,6%, and the students reading motivation improved 80,%. In the third cycle, students reading skill improved 91,4%, and the students reading motivation improved 91,4,%. It means that there is a significant improvement of reading motivation and skill which focused on discerning the main idea, specific information, understanding the sequence, and inference. All these suggest that improving reading motivation and skill by using literature circles is highly encouraged.